Pengaruh Penerapan E-Bupot Unifikasi dan E-Form terhadap Kepatuhan dalam Pelaporan Pajak Penghasilan : (Studi Empiris Klien Kantor Konsultan Pajak Edwin Suwandhy Semarang) - Fatasya Adelia Shifarani; Agus Hariyanto (Dharma Ekonomi, 2025)
This study aims to examine the influence of Perceived Ease and Perceived Usefulness of the Unified e-Bupot System and e-Form on Taxpayer Compliance. The population in this study consisted of corporate taxpayers who utilized the services of tax consultant Edwin Suwandhy. A random sampling technique was applied, resulting in 66 respondents being selected. This research follows a quantitative approach, using questionnaires as the data collection method. The data obtained from the samples were analyzed using a multiple linear regression model. The study’s findings reveal that the perceived ease of using the Unified e-Bupot system positively influences taxpayer compliance. The greater the understanding and familiarity corporate taxpayers have with the e-Bupot Unification system, the easier they find it to comply with income tax reporting regulations. On the other hand, the perceived usefulness of the e-Bupot Unification system does not have a significant impact on taxpayer compliance. This result suggests that the perceived benefits of the system are not sufficiently compelling to improve corporate taxpayer compliance. Similarly, the perception of ease and usefulness of e-Form also showed no significant effect on taxpayer compliance. This is likely because corporate taxpayers feel that the e-Form system is not easy to use, and the perceived advantages of the system are still considered insufficient to drive compliance. These findings emphasize the importance of improving both the ease of use and the perceived benefits of the e-Bupot and e-Form systems to enhance taxpayer compliance. Future policy improvements should focus on increasing user experience and addressing any gaps in the perceived utility of these tax reporting systems, especially for corporate taxpayers.